Comparison of sleep disorders in pregnant women with gestational diabetes mellitus and healthy women - Zohreh Yeganeh; Zohre Sheikhan; Alireza Zahiroddin; Nourossadat Kariman; Hedyeh Riazi; Fahimeh Kavossi (Mashhad University of Medical Sciences, 2019)
Introduction: Sleep disorders are of common problems during pregnancy. The rate of gestational diabetes (GDM) is increasing in Iran. Is gestational diabetes may cause sleep disorders during pregnancy? This study was performed with aim to compare sleep disorders in pregnant women with and without GDM. Methods: This comparative descriptive study was conducted on 240 pregnant women with gestational age of 22-32 weeks referring to health centers of Tehran ShahidBeheshti University of Medical Sciences in 2016. Case group consisted of 120 pregnant women with Fasting Blood Sugar>120 or Glucose Challenge Test>140 or abnormal Glucose Tolerance Test. Control group included 120 healthy pregnant women with normal blood sugar. Data collection tool were Pittsburgh Sleep Quality Index, Depression Anxiety Stress Scales- 21 and demographic characteristic questionnaires which were completed through interview. Data were analyzed using SPSS software (version 16), Mann-Whitney test and independent t test. P<0.05 was considered statistically significant. Results: Mean total sleep score was 17.37±5.79 in healthy women and 13.42±9.32 in women with GDM. Statistical significant difference was observed between two groups in terms of age, number of pregnancy and number of abortion (P<0.05). Mean scores of depression, anxiety, and stress were higher in women with GDM. Statistical significant difference was observed between two groups in terms of subjective sleep quality (P=0.005), sleep duration (P<0.001), and total score of sleep quality (P<0.001). Conclusion: Gestational diabetes can affect some dimensions of sleep. Sleep quality is lower in pregnant women with GDM than healthy pregnant women.